Development of Decentralized Finance in Comparable Indicators of the Financial Sector of the Economy - M. A. Abramova; S. V. Krivoruchko; O. V. Lunyakov; A. B. Fiapshev (Финансы: теория и практика)
The sphere of decentralized finance is the subject of widespread debate as the ways of providing services in the financial market. Using distributed registry technologies, smart contacts and a decentralized format of cooperation, it is capable, to a certain extent, of replacing traditional financial intermediaries in some product segments of the financial market. The authors set the task of identifying possible markers of liquidity flow into the sphere of decentralized finance, as well as assessing the scale and dynamics of its development compared with segments of the financial sector of the economy. The purpose of the study is to form a system of comparable indicators, based on which national regulators will be able to objectively assess the scale and dynamics of development of the DeFi sector. To achieve the goal, the article conducted a quantitative analysis of the relationship between changes in the money supply and the total value locked of crypto assets in the DeFi sector; a comparative analysis of various segments of the DeFi sphere and the financial sector of the economy was carried out. As the main methods, the authors used methods of regression analysis, systemic and logical methods, induction and deduction, methods of economic statistics, which made it possible to identify tendencies in the development of the sphere of decentralized finance against the background of indicators of development of the financial sector of the economy. The source data consisted of statistical databases on key indicators of the development of the financial sector of the economy at the international level, as well as databases on services provided by participants of decentralized finance. As a result of the study, the impact of changes in money supply on total value locked in DeFi is evaluated, as well as tendencies and scale of development of the sphere of decentralized finance in comparable indicators of the financial sector of the economy are identified. It is concluded that the scale of the current development of decentralized finance is not significant. However, according to a number of comparable indicators, this sphere already represents a certain parity with the financial sector of the economy. First of all, this applies to the trading turnover of decentralized exchanges and the volume of trading in crypto derivatives. The results of the study can be used by national regulators when assessing the scale of development of the sphere of decentralized finance under certain monetary and financial conditions.